2021
DOI: 10.3390/jmse9111152
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Study of Integrated Wet-Towing of a Triple-Bucket Jacket Foundation for Far-Offshore Applications

Abstract: As a form of clean and low-carbon green energy, offshore wind power occupies an important position in the global energy structure. With the rapid development of the wind power industry, wind power projects gradually develop from offshore to far-offshore sea areas. The multi-bucket jacket foundation is a considerable foundation type for far off-shore projects, but high installation costs involving ship transportation with parted components and field installation has significantly hindered its wide application. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…To validate the developed time-domain model and the WAMIT solutions with the modified NEWMODES, comparisons were made with the available experimental data in the literature. Although the relevant published data is not many so far, fortunately, we found that Yan et al (2021) [26] recently reported their experimental data which was therefore chosen in the numerical validations. In addition to the data in [26], more experimental data of their research work (obtained from the master dissertation [32]) was also employed in this work, which includes not only the stable towing stage but also the initial towing process.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To validate the developed time-domain model and the WAMIT solutions with the modified NEWMODES, comparisons were made with the available experimental data in the literature. Although the relevant published data is not many so far, fortunately, we found that Yan et al (2021) [26] recently reported their experimental data which was therefore chosen in the numerical validations. In addition to the data in [26], more experimental data of their research work (obtained from the master dissertation [32]) was also employed in this work, which includes not only the stable towing stage but also the initial towing process.…”
Section: Resultsmentioning
confidence: 99%
“…In this section, we first briefly introduce the experiments of [26] and then show the comparisons with the numerical solutions of the present time-domain model and the modified version of WAMIT. Following the numerical validations, more details of wet towing of suction bucket jacket, which may be to some extent challenging for direct experimental measurements, will be shown via time-domain simulations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations